Psychiatric symptom: asthenia - Чабан, Олег Созонтович (Psychological Counseling and Psychotherapy, 1970)
The article deals with the symptom as the most simple, the original (archaic) reaction of the body, which is the first manifestation of differentiated products of the human psyche in a pathological state. It was analyzed the relationship between the concepts and the symptom of the syndrome, the relationship of positive and negative disorders in the structure of the syndromes of pathomorphosis. It sets out a variety of conceptual approaches to the understanding of the specifics of the syndrome (Kraepelin, Goch, Bonhoeffer, Samohvalov). For example, phenomenology asthenia was shown that it can be considered as a single and comorbid syndrome, there is a problem of objectification of this syndrome (at the clinical, experimental psychological and subjective levels), especially in the dynamics.